Rancang Bangun Sistem Pembersih Akuarium Untuk Penjual Ikan Hias Jakarta Aquatics - Darmawan, Marten; Soewono, Arka Dwinanda; Hutagalung, Rory Anthony; Christiand, Christiand; Hermansyah, Fabian David (Jurnal Pengabdian Masyarakat Charitas, 2022)
Aquarium cleaning is routine maintenance that must be done to maintain dissolved oxygen levels in the water to ensure the survival of aquatic biota. Maintaining cleanliness and water quality is key to preventing the water in the aquarium from becoming cloudy and emitting a foul odor due to increased ammonia levels in the water. However, aquarium cleaning is quite time-consuming and laborious, which becomes a problem for Jakarta Aquatics, which is engaged in selling and purchasing ornamental fish. As a solution, a prototype cleaning equipment that can simplify the process of maintaining the cleanliness of the water in the aquarium was designed and built. In general, the cleaning equipment designed consists of an acrylic screen that acts as a pseudo-base that collects fish waste at the bottom of the aquarium tank. Pumps are then used to remove water and waste from the aquarium easily, so there is no need to remove aquarium inhabitants during the cleaning process, thereby minimizing the possibility of fish death due to stress. The method used during the outreach program includes conducting a survey, performing a design process, and demonstrating on how to use and maintain the cleaning equipment. To assess the success of this program, Jakarta Aquatics owners and employees were asked to fill out a questionnaire. The questionnaire results showed that partners were more than satisfied with the equipment performance and the demonstration event. It is hoped that using this cleaning equipment in their aquariums can help improve the productivity of Jakarta Aquatics employees.